First principles simulation of amorphous InSb - Los, Jan H.; Kühne, Thomas D.; Gabardi, Silvia; Bernasconi, Marco (Physical Review B - Condensed Matter and Materials Physics, 2013)
Ab initio molecular dynamics simulations based on density functional theory have been performed to generate a model of amorphous InSb by quenching from the melt. The resulting network is mostly tetrahedral with a minor fraction (10%) of atoms in a fivefold coordination. The structural properties are in good agreement with available x-ray diffraction and extended x-ray-absorption fine structure data and confirm the proposed presence of a sizable fraction of homopolar In-In and Sb-Sb bonds whose concentration in our model amounts to about 20% of the total number of bonds. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20